2022
DOI: 10.1155/2022/5408063
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dialectical Comprehensive Treatment of Traditional Chinese Medicine in Patients with Chronic Stable Heart Failure: A Randomized Controlled Trial

Abstract: The treatment of chronic stable heart failure (CSHF) with integrated traditional Chinese and Western medicine has been of wide concern. We mainly discuss the clinical efficacy of TCM decoction combined with acupuncture and moxibustion (A&M) in CSHF treatment on the basis of syndrome differentiation and treatment (SDT). The control group was given conventional cardiac rehabilitation (CCR), and the treatment group was given TCM decoction combined with A&M treatment based on SDT on the basis of convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…In the treatment group, Huoxue Wenyang Tang (Hwalhyeolonyang-tang, in Korean) was used in 2 studies, [ 23 , 24 , 29 ] Wenyang Buxin Tang (Onyangbosimtang, in Korean) in 1 study, [ 25 ] Xinshuai Qixu I Hao Fang (Shimsoigiheo1hobang, in Korean) in 1 study, [ 26 ] Sini Tang Jiajian (Sayeoktanggagam, in Korean) in 1 study, [ 27 ] and Fumai Tang (Bokmaektang, in Korean) [ 28 ] in 1 study. One study [ 30 ] combined Baoyaun Tang with Taohong Siwu Tang (Bowoontang hap Dohongsamultang, in Korean) or Zhenwu Tang with Xuefu Zhuyu Tang (Hyeolbuchukeotang, in Korean) or Gualou Xiebai Banxia Tang (Gwahroohaebaekbahnhahtang, in Korean) based on pattern identification. The most commonly used herbal medicines were Astragali Radix, Salviae Miltiorrhizae Radix, Liriopis Radix, and Ramulus Cinnamomi, which were used in 5 studies, while orally administered decoctions were used in all 7 study formulations (Appendix II, http://links.lww.com/MD/N256 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the treatment group, Huoxue Wenyang Tang (Hwalhyeolonyang-tang, in Korean) was used in 2 studies, [ 23 , 24 , 29 ] Wenyang Buxin Tang (Onyangbosimtang, in Korean) in 1 study, [ 25 ] Xinshuai Qixu I Hao Fang (Shimsoigiheo1hobang, in Korean) in 1 study, [ 26 ] Sini Tang Jiajian (Sayeoktanggagam, in Korean) in 1 study, [ 27 ] and Fumai Tang (Bokmaektang, in Korean) [ 28 ] in 1 study. One study [ 30 ] combined Baoyaun Tang with Taohong Siwu Tang (Bowoontang hap Dohongsamultang, in Korean) or Zhenwu Tang with Xuefu Zhuyu Tang (Hyeolbuchukeotang, in Korean) or Gualou Xiebai Banxia Tang (Gwahroohaebaekbahnhahtang, in Korean) based on pattern identification. The most commonly used herbal medicines were Astragali Radix, Salviae Miltiorrhizae Radix, Liriopis Radix, and Ramulus Cinnamomi, which were used in 5 studies, while orally administered decoctions were used in all 7 study formulations (Appendix II, http://links.lww.com/MD/N256 ).…”
Section: Resultsmentioning
confidence: 99%
“…The most commonly used herbal medicines were Astragali Radix, Salviae Miltiorrhizae Radix, Liriopis Radix, and Ramulus Cinnamomi, which were used in 5 studies, while orally administered decoctions were used in all 7 study formulations (Appendix II, http://links.lww.com/MD/N256 ). For acupuncture treatment, 3 studies [ 23 , 24 , 26 , 29 ] used acupuncture, 3 studies [ 25 , 27 , 28 ] used warm acupuncture, and 1 study [ 30 ] used a combination of acupuncture, auricular acupuncture, and moxibustion. The most commonly used acupuncture point was Neiguan (PC6), which was utilized in 6 studies [ 23 , 24 , 26 – 30 ] (Appendix III, http://links.lww.com/MD/N257 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have demonstrated that accurate treatment based on syndrome differentiation significantly enhances the efficacy of acupuncture and moxibustion. [44][45][46] Therefore, customizing the selection of acupuncture points according to the different types of mammary hyperplasia can improve the treatment effectiveness through strategic point selection. Sixthly, Empirical effect points are points selected by clinicians according to their own or others' clinical practice experience and have obvious curative effects on some diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Rational comprehensive treatment with TCM could effectively improve cardiac function and clinical treatment effects and is worthy of clinical application. [ 10 , 11 ] Heart failure is a major health problem worldwide. Traditional Chinese medicine alone or combined with modern medicine strategies can increase the success rate of cardiovascular disease treatment.…”
Section: Introductionmentioning
confidence: 99%